Modelling complex near-surface features to improve shallow seismic exploration. Issue 1 (1st December 2018) - Strong, Shaun
Abstract : Land seismic exploration is often limited or impacted by complex structures in the near surface. These can include large variations in velocities related to weathering (low velocity) or basalts (potentially high velocity). Timing changes due to near-surface velocity variations are often accommodated by applying statics corrections during seismic processing. Shallow coal exploration requires high-resolution data to image structures and faulting. A good understanding of these features is required for both safety and economic reasons. However, in some cases small errors in statics correction may have a significant impact on the viability of the use of seismic data in these complex environments. Often near-surface structures also show non-planar characteristics which may attenuate or further complicated the seismic response. In this paper we use finite-difference visco-elastic modelling to investigate the impact that a number of common near-surface structures have on seismic data. This modelling has been used to determine the optimal acquisition and processing parameters required for a seismic program in order to achieve desired results.